Wednesday

August 27, 2014

August 27, 2014

Posted by **Kiki** on Sunday, September 15, 2013 at 4:38pm.

- Math -
**Steve**, Sunday, September 15, 2013 at 4:56pm15xy+9y^2+6x^2 = 3(x+y)(2x+3y)

I think you can handle it from here, eh?

**Related Questions**

Math - the product (2x^4y)(3x^5y^8) is equivalent to? a.5x^9y^9 b.6x^9y^8 c.6x^...

Algebra 1 - Solve using two different methods. Explain which method you found to...

College Math - I need help with finding the slope and th y-intercept: 3y-2x=5+9y...

math - Solve the systems of equations by elimination. 1. -2x+y=7 2. 2x+y=-9 6x+...

Pre-Calculus - Solve by using the substitution method 1.x=-3y+4 and 3x+9y=12 3(-...

math, beginning algebra - Can someone correct this for me. Directions:Solve 6x-1...

Math help - Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using ...

Math - Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

math - 2x+3y=6 (solve for x) 2x+3y=6 Get unknown on one side and everything else...